Impacto de dietas com restrição de alimentos fonte de glúten em pacientes com fibromialgia - Ana Carolina Garcia de Las Ballonas Campolina (2017)
Fibromyalgia (FM) is a chronic and widespread pain condition, usually accompanied by several associated symptoms such as fatigue, sleep disorder, headache, irritable bowel syndrome and mood disorders. Recent studies point to the possibility of gluten protein having a role in the development of FM symptoms in a subgroup of patients. Our aim was to evaluate the impact of gluten-free diets on symptoms and inflammatory markers of FM, as well as to identify the presence of non-celiac gluten sensitivity (NCGS) in individuals with previous diagnosis of FM. For that, fourteen patients with FM diagnosis were kept on a diet restrict in gluten-free foods for a period 8 weeks. In the last weeks, they received rice protein isolate capsules (placebo) for 7 days, followed by a 3-day wash-out and a new challenge with capsules containing 6,3 g/day of gluten protein for another 7 days. In the initial period and in 8th week without gluten sources and after challenge with gluten, inflammatory markers were evaluated and questionnaires were carried out to evaluate the quantity and severity of FM symptoms and the impact of FM on daily routine. In addition, a questionnaire based on Salerno protocol was applied to evaluate the presence of NCGS. The results showed a reduction in the impact of FM in daily routine, number of FM symptoms and in the painful regions after 8 weeks of gluten-free diet. Nonetheless, gluten reintroduction was not associated with worsening of these results. There were no differences in the inflammatory markers in any experimental time. Consequently, the NCGS diagnosis was not confirmed in none patient. We concluded that the withdrawal of food sources of gluten from diet resulted in improvement of fibromyalgia. However, the reintroduction of gluten isolated caused no impact in the evaluated parameters, suggesting that gluten was not the factor responsible for the improvement of FM symptoms in the gluten-free period.